USE OF INDICATOR SAPROBIC ALGAE TO DETERMINE THE WATER QUALITY INDICATORS IN FISHERIES PONDS. (Scientific journal of the Fergana State University, 2026)
The results of our algological research conducted in the water bodies of several fishery farms in the Fergana Valley — Namanganbaliq, Damko‘l, and Yormozor — showed that during the period from 2009 to 2022, a total of 163 species and varieties of algae were identified, 42 of which were indicator-saprobic algae. These indicator-saprobic algae belong to 3 divisions, 7 classes, 9 orders, 14 families, and 24 genera, comprising 42 species and varieties in total.